Hiccups: an atypical presentation of lateral medullary syndrome - Zainulabid, Ummu Afeera; Che Mohamed, Siti Kamariah; Jaafar, Khairul Azhar (2021)
Background: Persistent hiccup related to lateral medullary syndrome is rarely reported as usually it resembles other gastrointestinal abnormality. It is often overlooked and can cause aspiration pneumonia.